An Immunoradiometric Assay for Factor VIII Related Antigen (VIIIRAg) Using Two Monoclonal Antibodies-Comparison with Polyclonal Rabbit Antibodies for Use in von Willebrand’s Disease Diagnosis - Sultan, Y; Avner, Ph; Maisonneuve, P; Arnaud, D; Jeanneau, Ch (Thrombosis and Haemostasis, 1984)
Two monoclonal antibodies raised against FVIII/von Willebrand protein were used in an immunoradiometric assay (IRMA) to measure this antigen in normal plasma and plasma of patients with different forms of von Willebrand’s disease. The first antibody, an IgG1 was used to coat polystyrene tubes, the second one, an IgG2a, iodinated and used in the second step. Both antibodies inhibit ristocetin induced platelet agglutination and react strongly with platelets, megacaryocytes and endothelial cells. The IRMA test using these antibodies showed greater sensitivity than that using rabbit polyclonal anti VIIIRAg antibodies. A good correlation between the two tests was nevertheless found when VIIIRAg was measured in the majority of patient’s plasma. However 5 patients from 3 different families showed more antigenic material in the rabbit antibody IRMA than in the monoclonal antibody IRMA. It is suggested therefore that the monoclonal antibodies identify part of the VIIIR:Ag molecule showing structural abnormalities in these vWd patients, these structural changes remaining undetected by the polyclonal antibodies.
Keywords: Monoclonal antibodies; von Willebrand’s disease; Hybridomas; Immunoradiometric assay